Factors associated with the development, progression, and outcome of dupuytren disease treatment: a systematic review - Geoghegan, L; Man, J; Jain, A; Price, A; Gibbons, E; Jerosch-Herold, C; Sidey-Gibbons, C; Rodrigues, JN (Ovid Technologies, 2021)
Background: The factors typically considered to be associated with Dupuytren disease have been described, such as those in the “Dupuytren diathesis.” However, the quality of studies describing them has not been appraised. This systematic review aimed to analyze the evidence for all factors investigated for potential association with the development, progression, outcome of treatment, or recurrence of Dupuytren disease.